PERANAN MATA KULIAH AL ISLAM KEMUHAMMADIYAHAN TERHADAP PERILAKU MAHASISWA UNIVERSITAS MUHAMMADIYAH TAPANULI SELATAN - Samsidar Samsidar; Darliana Sormin; Muksana Pasaribu (Al-Muaddib : Jurnal Ilmu-Ilmu Sosial & Keislaman, 2019)
Al-Islam courses and kemuhammadiyahan. Seharunya can provide enlightenment, become the basis of spiritual or religious and moral strength for the entire academic community who intellectually, can print students who are professionals in their fields. Al Islam and Kemuhammadiyah education can be a means to shape students' social behavior, including by instilling students to talk, behave politely and politely, and not hurt their friends, etc. Students are less interested in Al Islam and Kemuhammadiyah courses because they are not a main course. This causes students to only focus on mastery of the material and not live up to or practice the teachings contained therein. As a result, there are not many positive behaviors displayed by students after taking the course.Keywords: Al-Islam kemuhammadiyahan, behavior, students